How R&D Staff’s Improvisation Capability Is Formed: A Perspective of Micro-Foundations - He, Hui; Bai, Yan; Gao, Junguang; Xie, Jinqiang (Frontiers in Psychology, 2020)
The study examines how R&D staff improvisation capability is formed based on theory of micro-foundations, that is, how R&D individuals, experience and external knowledge gathering, and minimal structure interact and work on their improvisation capability together. The results show that: (1) R&D staff’s experience and external knowledge gathering have linear influences on their improvisation capability, respectively; (2) minimal structure has a curvilinear impact on improvisation capability; (3) minimal structure has a curvilinear moderating effect on the relationship between experience, external knowledge gathering and improvisation capability, respectively. The study suggests that managers keep minimal structure at the moderate level to promote their R&D people’s improvisation capability.